2021
DOI: 10.1186/s12974-021-02315-8
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4-induced Müller cell gliosis and TNF-α elevation-mediated retinal ganglion cell apoptosis in glaucomatous rats via JAK2/STAT3/NF-κB pathway

Abstract: Background Glaucoma, the leading cause of irreversible blindness worldwide, is a type of retinal disease characterized by the selective death of retinal ganglion cells (RGCs). However, the pathogenesis of glaucoma has not been fully elucidated. Transient receptor potential vanilloid 4 (TRPV4) is a pressure-sensitive and calcium-permeable cation channel. TRPV4 is widely distributed in the retina and its sustained activation leads to RGC death; indicating that TRPV4 may be a possible target for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…For instance, VEGF release, particularly the isoform VEGFA [ 179 , 180 ], in combination with reactive oxygen species (ROS) production in diabetic retinopathy has been shown to enhance retinal degeneration [ 181 ], whereas VEGFD is protective for RGCs and the retinal vasculature [ 182 ]. In addition, the secretion of TNF-α has been shown to exert early neuroprotective effects [ 183 ] but to ultimately induce Müller cell gliosis and RGC death in the glaucomatous retina [ 184 ]. Upon a neuroinflammatory insult, the quiescent and neuroprotective Müller glia undergo reactive, proliferating gliosis [ 185 ], which in turn enhances pathological angiogenesis [ 186 , 187 ] and increases RGC vulnerability to retinal injury [ 169 ].…”
Section: Glutamate Excitotoxicity In the Retinamentioning
confidence: 99%
“…For instance, VEGF release, particularly the isoform VEGFA [ 179 , 180 ], in combination with reactive oxygen species (ROS) production in diabetic retinopathy has been shown to enhance retinal degeneration [ 181 ], whereas VEGFD is protective for RGCs and the retinal vasculature [ 182 ]. In addition, the secretion of TNF-α has been shown to exert early neuroprotective effects [ 183 ] but to ultimately induce Müller cell gliosis and RGC death in the glaucomatous retina [ 184 ]. Upon a neuroinflammatory insult, the quiescent and neuroprotective Müller glia undergo reactive, proliferating gliosis [ 185 ], which in turn enhances pathological angiogenesis [ 186 , 187 ] and increases RGC vulnerability to retinal injury [ 169 ].…”
Section: Glutamate Excitotoxicity In the Retinamentioning
confidence: 99%
“…Mechanistically, we propose that METTL3 promotes the m6A methylation of SOCS3 mRNA, and then YTHDF1 recognizes and binds to the m6A-containing mRNA of SOCS3 and promotes SOCS3 protein expression. Previous studies have demonstrated that the JAK2–STAT3 pathway is involved in the expression and secretion of the inflammatory cytokines TNF-α and IL-1β ( 33 , 34 ). Our results further suggest that YTHDF1 and SOCS3 negatively regulate the inflammatory response by regulating the JAK2–STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another channel through which ganglion cell apoptosis may be mediated is TRPV4. Immunochemistry has shown that a substantial amount of TRPV4 is localized in RGCs and the plexiform layers in the rat and porcine retinas (150,151). In many species, TRPV4 has been observed in RGC dendrites, somas and axon bundles in the retina, the optic nerve head, and the laminar region of the optic nerve (121,150,(152)(153)(154).…”
Section: Trp Channels In the Optic Nerve And Trabecular Meshwork (Tm)...mentioning
confidence: 99%
“…Inhibition of TRPV4 channels within the retina has been reported to improve the survival of RGCs ( 150 ). Also, intraocular injection of TRPV4 antagonists has been found to lower IOP in glaucomatous mouse eyes and to protect retinal neurons from IOP-induced cell death by mediating the JAK2/STAT3/NF-κB signaling pathway ( 151 ). These findings indicate that inhibition of TRPV4 could be used as a potential treatment for glaucoma.…”
Section: The Expression Of Trp Channels In Ocular Tissues and The Pat...mentioning
confidence: 99%